Conditional deletion of the AMPA-GluA1 and NMDA-GluN1 receptor subunit genes in midbrain D1 neurons does not alter cocaine reward in mice - Borruto, Anna Maria; Calpe-López, Claudia; Spanagel, Rainer; Bernardi, Rick E. (Neuropharmacology, 2024)
Synaptic plasticity in the mesolimbic dopamine (DA) system contributes to the neural adaptations underlying addictive behaviors and relapse. However, the specific behavioral relevance of glutamatergic excitatory drive onto dopamine D1 receptor (D1R)-expressing neurons in mediating the reinforcing effect of cocaine remains unclear. Here, we investigated how midbrain AMPAR and NMDAR function modulate cocaine reward-related behavior using mutant mouse lines lacking the glutamate receptor genes Gria1 or Grin1 in D1R-expressing neurons (GluA1D1CreERT2 or GluN1D1CreERT2, respectively). We found that conditional genetic deletion of either GluA1 or GluN1 within this neuronal sub-population did not impact the ability of acute cocaine injection to increase intracranial self-stimulation (ICSS) ratio or reduced brain reward threshold compared to littermate controls. Additionally, our data demonstrate that deletion of GluA1 and GluN1 receptor subunits within D1R-expressing neurons did not affect cocaine reinforcement in an operant self-administration paradigm, as mutant mice showed comparable cocaine responses and intake to controls. Given the pivotal role of glutamate receptors in mediating relapse behavior, we further explored the impact of genetic deletion of AMPAR and NMDAR onto D1R-expressing neurons on cue-induced reinstatement following extinction. Surprisingly, deletion of AMPAR and NMDAR onto these neurons did not impair cue-induced reinstatement of cocaine-seeking behavior. These findings suggest that glutamatergic activity via NMDAR and AMPAR in D1R-expressing neurons may not exclusively mediate the reinforcing effects of cocaine and cue-induced reinstatement.
Online verfügbar: 14. Juli 2024, Artikelversion: 15. Juli 2024
Gesehen am 25.11.2024